2021
DOI: 10.1038/s41598-021-01743-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and internal validation of an algorithm to predict intraoperative risk of inadvertent hypothermia based on preoperative data

Abstract: Intraoperative hypothermia increases perioperative morbidity and identifying patients at risk preoperatively is challenging. The aim of this study was to develop and internally validate prediction models for intraoperative hypothermia occurring despite active warming and to implement the algorithm in an online risk estimation tool. The final dataset included 36,371 surgery cases between September 2013 and May 2019 at the Vienna General Hospital. The primary outcome was minimum temperature measured during surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…At present, most medical staff has recognised the harm of perioperative hypothermia, and they gradually started to use the predictive model and take early preventive measures to prevent perioperative hypothermia. Studies have shown that the intraoperative prediction model of patients undergoing general anaesthesia surgery can effectively predict and prevent the occurrence of intraoperative hypothermia in such patients (Wallisch et al, 2021; Yi & Zhan et al, 2017). For example, the prediction model of hypothermia during caesarean section constructed by Desgranges (Desgranges et al, 2017) addressed the prediction and intervention of hypothermia during caesarean section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, most medical staff has recognised the harm of perioperative hypothermia, and they gradually started to use the predictive model and take early preventive measures to prevent perioperative hypothermia. Studies have shown that the intraoperative prediction model of patients undergoing general anaesthesia surgery can effectively predict and prevent the occurrence of intraoperative hypothermia in such patients (Wallisch et al, 2021; Yi & Zhan et al, 2017). For example, the prediction model of hypothermia during caesarean section constructed by Desgranges (Desgranges et al, 2017) addressed the prediction and intervention of hypothermia during caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Hosmer–Lemeshow can test the model's goodness of fit, and the AUC value (Area under the ROC curve) is used to evaluate the pros and cons of the model (Benhalima et al, 2020; Damen et al, 2019). In recent years, intraoperative hypothermia risk prediction models have been explored in laparoscopic surgery, caesarean section, general anaesthesia and other surgical fields (Desgranges et al, 2017; Wallisch et al, 2021; Yi & Zhan et al, 2017). However, patients undergoing joint replacement surgery are in their old age and receive mainly spinal anaesthesia; additionally, the surgery needs a large incision.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that intraoperative body temperatures even as low as 35.5 °C were not associated with adverse outcomes [ 13 ]. We recently showed that hypothermia defined by body temperature falling below thresholds of 36 °C and 35.5 °C at least at a single time point can be predicted with acceptable performance using logistic regression [ 14 ]. However, the definition of hypothermia used in this study may be imprecise when applied to our dataset, as nearly half of all patients in our cohort crossed the <36 °C threshold, even though average body temperature during anesthesia was above >36°.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating the risk of inadvertent hypothermia could enable the targeted use of thermal care interventions and thereby optimize the use of these potentially limited resources. We recently developed several regression models to predict intraoperative hypothermia of less than 36 °C and less than 35.5 °C with sufficient accuracy [ 14 ]. However, in this study, hypothermia was defined as point incidence of body temperature below two fixed and arbitrary thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Low preoperative baseline body temperature is the most related factor for intraoperative hypothermia. After general anesthesia, patients with low preoperative baseline body temperature are more likely to develop hypothermia due to redistribution of body temperature [ [19] , [20] , [21] , [22] , [23] ].…”
Section: Discussionmentioning
confidence: 99%